(untitled) (Bangladesh Critical Care Journal, 2021)
The coronavirus disease 2019(COVID-19) pandemic poses an extraordinary challenges to patients, communities and overall health care systems. It has resulted in millions of people infected worldwide and has indirectly devastated even more individuals with prolonged post-infectious symptoms. The burden of survivors having post-COVID symptoms is likely to be huge. Multidisciplinary post-COVID-19 clinics are now playing a pivotal role addressing both persistent symptoms and potential long term sequelae. In this review, we tried to summarize the adverse health outcomes based on current evidences, assess the potential risk of long-term complications and make certain recommendations. Bangladesh Crit Care J March 2021; 9(1): 38-40